A New Approach for Documenting Architectural Cultural Heritage: The Case Study Of Asinou Church In Cyprus - Themistocleous, Kyriacos; Ioannides, Marinos; Agapiou, Athos; Hadjimitsis, Diofantos G. (My University, 2015)
The documentation of architectural cultural heritage sites has traditionally been labor-intensive. New innovative technologies provide an affordable, reliable and straightforward method of capturing cultural heritage sites, thereby providing a more efficient and sustainable approach to documentation of cultural heritage monuments and sites that architects, archeologists and cultural heritage experts can use for data acquisition, archive, process, share and visualize for documentation, restoration, preservation and rehabilitation purposes. This paper focuses on a new novel approach used in several EU Research projects, to document the UNESCO WHL site of Asinou Church in Cyprus (http://www.byzantinecyprus.com/) using various modern techniques, such as UAV, photogrammetry and 3D printing. Hundreds of images from the monument were taken using a UAV with an attached high resolution camera. The images were processed to generate an accurate digital 3D model and reproduced using a 3D printer. Such a methodology provides architects, archaeologists, civil engineers and cultural heritage experts an accurate, simple and cost-effective method of documenting cultural heritage sites and generating digital 3D models using novel techniques and innovative methods. This approach can also be used in urban or rural environments to document large scale sites which traditionally are time-consuming and labor-intensive.
Proceedings of the International Conference on Sustainability in Architecture and Cultural Heritage
Keywords: Cultural heritage; Architecture; Documentation; 3D models